Mikrobiota Usus dan Gut-lung Axis pada Penyakit Paru - Fitri Nur Malini S (UMSU, 2021)
Gut has a bidirectional connection with lung. This is often called the gut-lung axis. Most lung diseases have high morbidity, mortality and disability. This is due to the inflammatory process. This inflammatory process not only caused physiological changes in the lungs, but also caused pathological conditions in the gut. Likewise, if gut health is not maintained, causing intestinal dysbiosis, it also has the potential for translocation or expansion of bacteria from the intestine to other organs. Therefore, providing intervention to the gut to maintain the balance of gut microbiota has been shown to improve inflammatory status and lung disease susceptibility. The intervention given can be in the form of probiotics or prebiotics..